PENDAMPINGAN DAN TEACHING TECHNOLOGI INDUSTRI RUMAH TANGGA (IRT) KUEMICEL DALAM PENGOLAHAN PRODUK BERBAHAN BAKU IKAN GABUS DI TALANG BETUTU, PALEMBANG - Guttifera, Guttifera; Dendi, Dendi; Sari, Selly Ratna (Universitas Mataram, 2024)
Efforts to efficiently utilize fishery products and economic value to extend the shelf life of fish are called fisheries processing. Traditional market markets and household-scale industries still dominate the fishery processing industry. Home Industry (IRT) fishery products in Palembang is IRT Kuemicel. Application of technology capable of processing fishery products (Snackhead fish). The selection of snakehead fish as raw material is seen from the characteristics of fish meat, nutritional ingredients, and the supply of this type of fish in the Palembang area. The purpose of this activity is to increase the knowledge and skills of processing fishery products for Kuemicel IRT’s so as to produce products made from Snackhead fish that are more attractive and have high nutritional content. This activity aims to improve knowledge and skills in processing fishery products for IRT Kuemicel, the methods of activities used include FGD, Training, Tool Provision, and Evaluation. artners' knowledge and skills increased regarding the processing of snakehead fish. Partners have been able to produce processed snakehead fish products (pempek, kemplang and petty snakehead fish) which have their own advantages compared to existing products in the market. In addition, partners' knowledge and skills have also increased in the field of marketing. Partners know marketing management including sales with internet technology, namely digital marketing and social media as a product catalog. Partners develop marketing and promotional media by improving advertisements and posts on social media and providing a more attractive product appearance than before. The service activities that have been carried out at IRT Kuemicel help solve problems in partners so that partners can produce products that meet standards in large enough quantities, of course, saving costs and production time.